2019
DOI: 10.1111/apa.14922
|View full text |Cite
|
Sign up to set email alerts
|

High daily salt intake had a negative impact on how well nocturnal enuresis treatment worked on children aged 7‐10 years

Abstract: Aim We investigated whether the daily salt intake of children with nocturnal enuresis influenced their response to 1‐desamino‐8‐D‐arginine vasopressin therapy. Methods This study comprised 129 children (67.4% boys) with a median age of 9.2 years (range 7.2‐10.4) with monosymptomatic nocturnal enuresis who were seen at Kansai Medical University Hospital, Osaka, Japan, from 2013 to 2017. Urinary sodium concentrations were determined using a spot urine test, and the children were divided into appropriate (n = 55)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The treatment response was then compared 1 month after the start of DDAVP treatment. The results showed that the percentage of patients who exhibited a “partial response” or better to treatment was 30.8% in the standard salt intake group and 12.0% in the high salt intake group, indicating that the high salt intake group was less responsive to treatment 31 . After patients and their parents were given salt‐reduction advice, the DDAVP treatment response was then evaluated in 24 children with nocturnal enuresis whose estimated daily salt intake had been determined to be excessive.…”
Section: How To Manage Patients With Desmopressin Treatment Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…The treatment response was then compared 1 month after the start of DDAVP treatment. The results showed that the percentage of patients who exhibited a “partial response” or better to treatment was 30.8% in the standard salt intake group and 12.0% in the high salt intake group, indicating that the high salt intake group was less responsive to treatment 31 . After patients and their parents were given salt‐reduction advice, the DDAVP treatment response was then evaluated in 24 children with nocturnal enuresis whose estimated daily salt intake had been determined to be excessive.…”
Section: How To Manage Patients With Desmopressin Treatment Resistancementioning
confidence: 98%
“…The results showed that the percentage of patients who exhibited a "partial response" or better to treatment was 30.8% in the standard salt intake group and 12.0% in the high salt intake group, indicating that the high salt intake group was less responsive to treatment. 31 After patients and their parents were given salt-reduction advice, the DDAVP treatment response was then evaluated in 24 children with nocturnal enuresis whose estimated daily salt intake had been determined to be excessive. Of the 24 patients who were instructed to reduce salt intake, salt intake was reevaluated 4 to 8 weeks later and divided into two groups: 17 patients whose salt intake decreased (the reduced salt group) and seven patients whose salt intake did not decrease (the unchanged group).…”
Section: How To M a Nage Pat I E N T S W I T H De Smopr E S Si N T R ...mentioning
confidence: 99%
“…The results showed a higher response rate and a lower number of relapses in those who received desmopressin and dietary advice compared to those who received desmopressin alone (13). Another study by Tsuji et al in Japan showed that the high daily salt intake significantly reduced the efficacy of desmopressin in the treatment of nocturnal enuresis; thus, salt consumption should be controlled in children with nocturnal enuresis (14).…”
Section: Dietary Recommendationmentioning
confidence: 99%